# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-6 y^{\prime }+34 y = {\mathrm e}^{3 t} \tan \left (5 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+34 y = {\mathrm e}^{5 t} \cot \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-12 y^{\prime }+37 y = {\mathrm e}^{6 t} \sec \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+17 y = {\mathrm e}^{4 t} \sec \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = \frac {1}{1+{\mathrm e}^{3 t}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-25 y = \frac {1}{1-{\mathrm e}^{5 t}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 2 \sinh \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{t}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 t}}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+16 y = \frac {{\mathrm e}^{-4 t}}{t^{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = \frac {{\mathrm e}^{-3 t}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = {\mathrm e}^{-3 t} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = \cos \left ({\mathrm e}^{t}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{-2 t} \sqrt {-t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \sqrt {-t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = {\mathrm e}^{5 t} \ln \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = {\mathrm e}^{2 t} \arctan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+16 y = \frac {{\mathrm e}^{-4 t}}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (\frac {t}{2}\right )+\csc \left (\frac {t}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \tan \left (3 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sec \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \tan \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sec \left (3 t \right ) \tan \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sec \left (2 t \right ) \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \frac {\csc \left (3 t \right )}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sec \left (2 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-16 y = 16 t \,{\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \tan \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sec \left (2 t \right )+\tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \csc \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+3 y = 65 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = {\mathrm e}^{-\frac {t}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-10 y^{\prime \prime }+25 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}8 y^{\prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime \prime }-4 y^{\prime \prime }-5 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime \prime }-5 y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-5 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime \prime }-15 y^{\prime }+11 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-9 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }-y^{\prime \prime }+54 y^{\prime }-72 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+7 y^{\prime \prime \prime }+6 y^{\prime \prime }-32 y^{\prime }-32 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+12 y^{\prime \prime \prime \prime }+48 y^{\prime \prime }+64 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}24 y^{\prime \prime \prime }-26 y^{\prime \prime }+9 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}8 y^{\left (5\right )}+4 y^{\prime \prime \prime \prime }+66 y^{\prime \prime \prime }-41 y^{\prime \prime }-37 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\left (5\right )}+7 y^{\prime \prime \prime \prime }+17 y^{\prime \prime \prime }+17 y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+8 y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime \prime }+16 y^{\prime }-26 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+12 y^{\prime \prime \prime }+60 y^{\prime \prime }+124 y^{\prime }+75 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+30 y^{\prime \prime }-56 y^{\prime }+49 y = 0
\] |
✓ |
✓ |
|
\[
{}\frac {31 y^{\prime \prime \prime }}{100}+\frac {56 y^{\prime \prime }}{5}-\frac {49 y^{\prime }}{5}+\frac {53 y}{10} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-y^{\prime \prime \prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+9 y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+9 y^{\prime \prime } = 9 \,{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+10 y^{\prime \prime }+34 y^{\prime }+40 y = t \,{\mathrm e}^{-4 t}+2 \,{\mathrm e}^{-3 t} \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 2 \,{\mathrm e}^{-3 t}-t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }+13 y^{\prime \prime }-24 y^{\prime }+36 y = 108 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+6 y^{\prime \prime }-14 y^{\prime }-104 y = -111 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-10 y^{\prime \prime \prime }+38 y^{\prime \prime }-64 y^{\prime }+40 y = 153 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = \sec \left (2 t \right ) \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = \sec \left (2 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = \tan \left (2 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime } = \sec \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = -\sec \left (t \right ) \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = \sec \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime } = -\frac {1}{t^{2}}-\frac {2}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = \frac {{\mathrm e}^{t}}{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-4 y^{\prime \prime }-11 y^{\prime }+30 y = {\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-10 y^{\prime }-24 y = {\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-13 y^{\prime }+12 y = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime } = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+y^{\prime \prime \prime \prime } = -24
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \tan \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime } = 3 t^{2}
\] |
✓ |
✓ |
|